Bridging the rural-urban dichotomy in land use science - Vliet, Jasper van; Birch-Thomsen, Torben; Gallardo, Marta; Hemerijckx, Lisa-Marie; Hersperger, Anna M.; Li, Mengmeng; Tumwesigye, Samuel; Twongyirwe, Ronald; Rompaey, Anton van (Journal of Land Use Science, 2020)
Rural and urban areas are often conceptualized as two separate entities and studied accordingly. However, in reality, they are related in multiple ways. Here we explore this relation between rural and urban areas from a land use perspective. We argue that land should be characterized along a gradient from rural to urban. Further, we argue that land use along this gradient typically combines both rural and urban functions. Finally, we point at the complex patterns of migration and mobility between different types of settlements, which is a multidirectional process that further blurs the distinction between rural and urban areas. These propositions are supported by examples from recent research and suggest the need for a more inclusive approach towards the analysis of rural and urban land use systems, as well as plans and policies that target these systems
Keywords: Rural-urban gradient; Rural urbanization; Agricultural transition; Land use planning; Settlement systems